Participating in the New Creation in Ephesians - Mark J. Keown (Religions)
This article explores Ephesians, asking how the theme of the new creation is developed in Ephesians. Rather than specifying matters like authorship, date, and recipients, it takes a broad view of the situation of the letter so that the focus can be on exploring the theme. It argues that the new creation idea is developed in three main ways. First, while Ephesians has a decidedly realized eschatology, there are hints throughout the letter of the consummation when the whole Earth is freed from corruption and reconciled under one head, Jesus Christ. Second, particularly in chapters 1–3, the writer of Ephesians focuses on realized aspects of eschatology to strengthen the readers’ understanding of their identity in Christ and their status as people of the new creation. The writer does this to strengthen the readers to assume the posture of the new creation while living in a fallen world beset with sin and under spiritual powers. In Ephesians 4–6, the writer describes this new creation virtues the readers are to embody as they contend for God in the world. Finally, the article explores the missional appeal of the letter. The writer challenges the readers to embody the new creation ethic and join God’s mission that calls all humankind to believe in the gospel and become people of the new creation.